The Effect of Proportion of Dioscorea alata and Wheat Flour on the Acceptability of Steamed Bolu: Pengaruh Proporsi Tepung Umbi Uwi (Dioscorea alata) dan Tepung Terigu Terhadap Daya Terima Bolu Kukus - Naimah, Siska Yulva; Ulilalbab, Arya; Suprihartini, Cucuk (Universitas Muhammadiyah Sidoarjo, 2023)
Uwi tuber is functional food ingredients than can be flourished to become further food preparations. Uwi tuber is one of the recommended foodstuffs for diabetics with diabetes mellistusas alternative of first food. It is because uwi tuber has lower glicemix index compared to other foodstuffs, such as rice, corn, etc. Based on the potential of the uwi tuber, it is necessary to do further innovation in food processing, one of them is to be processed as another food such as steamed bolu which has low glicemix index. The purpose of this study is to know the effect of uwi tuber flour and wheat flour proportion toward acceptability of steamed bolu. This study was conducted at the Food Technology Laboratory of Nutrition Academy KaryaHusada Kediri on 29 February 2019 by using an experimental method with a Complete Randomized Design with 3 treatments and 3 times replications, namely P0uwi tuber flour : wheat flour (0% : 28%), P2uwi tuber flour : wheat flour (14% : 14%), P3uwi tuber flour : wheat flour (21% : 7%). Statistical analysis of organoleptic test uses Friedman Rank. According to organoleptic test that has been done, it is obtained steamed bolu in the propostion of uwi tuber flour : wheat flour (21% : 7%) can be accepted organoleptically. However, there is a need for research on the differences in handling during the pouring flour process as the basis production of steamed bolu.